“I’VE GOTTA DO IT FOR THE BIT”: MEMETIC MEDIA AND COLLECTIVE IDENTITY THROUGH STREAMER PERFORMANCE ON TWITCH - Jackson, Nathan J (AoIR Selected Papers of Internet Research, 2020)
Videogame livestreamers on the platform Twitch present a carefully curated version of themselves negotiated in part via interactions with their viewers. This persona is encoded not just through their live performance, but also through other platform features including streamer-specific emoticons and audio-visual overlays triggered by stream events such as donations and subscriptions. From these customisable features emerges a complicated feedback loop between the streamer and non-streamer participants that ultimately results in a set of collective values performed and refined by both parties over time. In this paper I interrogate how the incorporation of Internet memes into streaming personas creates accessible avenues for communication with and between members of this collective that contribute significantly to this value system. I do this by defining the term memesis as the cultural process by which Internet users draw upon existing memes in order to create new memetic media. Through two contrasting case studies of Twitch streamers BrownMan and PaladinAmber, I examine how memesis reflects streamer agency and impacts the structure and values of stream collectives. In particular, I draw attention to the relationship between memes and stream collectives as it relates to streamer identity, memetic histories within streams, and the contrasting explicit and latent values within manifestations of particular memes, among others. Further, understanding how memesis renders visible the encoding of meaning and value into manifestations of meme by emphasising the creation process over the memetic product, I argue that the concept has value not just on Twitch, but within broader digital cultural spheres.